East Java Online Transactions: Demand Side Analysis - Astuti, Riska Dwi; Fazira, Nadia (Universitas Airlangga, 2019)
Despite the study of rapid growth of online-based transactions in East Java over the past few years, little is focused on the demand side in which consumer characteristics are crucial in this event. This study aims to analyze the relationship of consumer characteristics on the expansion of online-based transactions in East Java. Panel data consisting of 38 districts/cities in East Java province in the period 2015-2017 is analyzed using the random effects method. The results show that the increase of tertiary education participation has a significant positive effect on digital transactions both for goods/service transaction and the use of banking facilities. In addition, mobile phones ownership also has a significant positive role in improving online transactions for the sale and purchase of goods services through the internet. Share of non-food expenditure has a positive effect on online transactions, especially for financial transactions. On the other hand, the productive age population has a negative significant effect on online buying and selling activities. Health variable insignificantly affects online transactions since the activities of transactions through the internet can be done both in healthy and unhealthy conditions. Likewise with computer ownership that does not significantly affect online transactions because people tend to use mobile phones as the transaction device. Level of expenditure does not affect online transactions because online transactions have become the lifestyle in this digital era. Thus, the internet-based transaction is no longer influenced by economic conditions. Keywords: Transactions, Online, Random Effects, Consumers. JEL: G230, G400, O330